Modulating Factors in the Development of Motion Sickness in Transportation Vehicles: Malaysia Case Study - Mohd Iyad Akmal Mohd Indra Sefee; Juffrizal Karjanto; Muhammad Zahir Hasan; Fauzi Ahmad; Abd Fathul Hakim Zulkifli; Syabillah Sulaiman; Zulhaidi Mohd Jawi; Matthias Rauterberg (Automotive Experiences, 2026)
Motion sickness (MS) is a common issue for vehicle passengers, characterized by symptoms such as nausea, dizziness, and discomfort due to sensory conflicts between the visual and vestibular systems. This study aims to identify and quantify the modulating factors contributing to MS in vehicles within the Malaysian context. A systematic questionnaire was conducted, incorporating subjective feedback from 634 participants. The results highlight key factors like seating position, visual activities, and environmental conditions that influence MS susceptibility showing the most prominent factors are from Visual Activity with a mean of 3.44 among the others contributing most susceptibility from the activities of Reading (83.2%) and Writing (79.2%). Older people and females seemed to report greater susceptibility to motion sickness. This vulnerability is shown to increase with age as those 45+ years and above show the highest susceptibility, reporting a 69% rate on curvy roads and 66% during reading, in contrast with those between 18-29 who report a 52% and 50% susceptibility rate. Females again reported consistently higher rates than males, with the difference being larger in situations involving rear-facing seating or tasks requiring significant visual focus, such as reading (female 63% vs. male 46%) and driving on curvy roads (female 68% vs. male 50%). These factors of rear-facing seating and tasks involving intense visual focus, like reading or watching videos, were the strongest modulators identified, with a strong aggravating influence on symptoms across all groups. The findings provide crucial baselines for engineering future vehicle layouts, optimizing cabin climate systems, and designing targeted mitigation systems required to support human comfort and accelerate Automated Vehicle (AV) adoption in developing transport infrastructures.